(untitled) (Journal of Preventive and Social Medicine, 2021)
Background: This study aimed to assess the extent of socio-demographic factors that affect food insecurity among rural school going children. Methods: A school based cross-sectional study was conducted among 460 rural school going children (class 4 to class I 0) in Saltha upaziila of Faridpur district, Bangladesh from January-December, 2019. Children providing assent after getting consent from their parents were inducted as study participants. Semi-structured questionnaire was used to collect data on the food insecurity and socio-demographic variables. The study was conducted in Saltha upaziila of Faridpur district, Bangladesh from January-December, 2019 Results: Among the participants about 59.3% were moderately food insecure which means they were deprived of psychological and physical access to food. 53.7% were female and 88.3% of them were Muslims , 30.7% were from class 8, 70.7% were from nuclear family, 93% had siblings , 92% resided into house on their own land , 78.5% had own agricultural land and in 52.7% cases participant’s father were farmer and their mean income was 98208.18 ± 13618.196 Taka per. 35.2% lived in both Semi Pucca house and Tin Shade house and 7 I% had domestic animal in their hou se, such as goat, sheep, cow, duck, hen etc., 41.5% had television in their house but 52% didn’t have refrigerator in their house. There was a statistically significant relationship between food insecurity and age of participants (p- 0.000),educational status (p- 0.000),head of family (p- 0.008),occupation of father (p- 0.0IO). yearly ineome of family member (p-0.000), house type (p-0.000). Conclusion: National policies and programs need to stress on how to improve family income earning capacity and socioeconomic status to handle food insecurity. JOPSOM 2020; 39(1): 67-72